Statistical Modelling of Extreme Data of Air Pollution in Pekanbaru City - Ari Pani Desvina; Elfira Safitri; Ade Novia Rahma (Department of Mathematics, Faculty of Sciences and Technology, UIN Syarif Hidayatullah, 2019)
AbstractAir pollution is a phenomenon that is often discussed, especially regarding air quality in urban areas. This has become a major contributor to health problems and environmental issues in Asian countries, such as Indonesia, especially Riau Province. The event of forest fires is one of the many events that occurred in Indonesia, especially Riau Province which harmed the population of Indonesia and neighboring countries. The phenomenon of forest forestry generally occurs due to a shift in the season towards drought and can occur in areas prone to forest fires. Therefore, it is necessary to know the model of air pollution distribution by Particulate Matter (PM10) in Pekanbaru City. This study aims to obtain the distribution model for daily air pollution PM10 in Pekanbaru City from 2014 to February 2015. Data was taken from three stations i.e. Sukajadi Station, Tampan Station, and Kulim Station. Four distributions will be tested i.e. Log Pearson III distribution, Gumbel distribution, Generalized Pareto Distribution, and Generalized Extreme Value (GEV) distribution. We test the goodness of fit from these distribution using the Kolmogorov-Smirnov and the Anderson-Darling tests. The result shows that the Generalized Extreme Value (GEV) distribution model was better than the Log Pearson III, Gumbel and Generalized Pareto distribution models for modeling city air pollution data Pekanbaru with three stations namely Sukajadi, Tampan, and Kulim.Keywords: Anderson-Darling; Generalized Extreme Value (GEV); Kolmogorov-Smirnov. AbstrakPencemaran udara merupakan satu fenomena yang sering dibicarakan, apalagi mengenai kualitas udara di daerah perkotaan. Hal ini menjadi penyumbang utama tentang masalah kesehatan dan isu lingkungan hidup di negara-negara Asia, seperti Negara Indonesia khususnya Provinsi Riau. Peristiwa kebakaran hutan merupakan salah satu peristiwa yang banyak terjadi di Indonesia khususnya Provinsi Riau yang berdampak negatif terhadap penduduk Indonesia dan negara tetangga. Fenomena kebarakan hutan pada umumnya terjadi karena adanya pergeseran musim kearah kemarau dan dapat terjadi di daerah rawan kebakaran hutan. Oleh karena itu, perlu diketahui model distribusi pencemaran udara oleh Particulate Matter (PM10) Kota Pekanbaru. Penelitian ini bertujuan untuk mendapatkan model distribusi data harian pencemaran udara oleh Particulate Matter (PM10) Kota Pekanbaru Tahun 2014 sampai Februari 2015 dengan tiga stasiun yaitu stasiun sukajadi, stasiun tampan dan stasiun kulim. Adapun distribusi yang digunakan adalah distribusi Log Pearson III, distribusi Gumbel, Distribusi Generalized Pareto dan distribusi Generalized Extreme Value (GEV). Berdasarkan pembahasan uji kebaikan (Goodness of Fit) yaitu uji Kolmogorov-Smirnov dan Anderson-Darling, maka diperoleh bahwa model distribusi Generalized Extreme Value (GEV) lebih baik dari pada model distribusi Log Pearson III, Gumbel dan Generalized Pareto untuk memodelkan data pencemaran udara kota Pekanbaru dengan tiga stasiun yaitu Sukajadi, Tampan dan Kulim.Kata Kunci: Anderson-Darling, Generalized Extreme Value (GEV), Kolmogorov-Smirnov